Climbing a Wall: Strategic Litigation Against Automated Systems in Migration and Asylum - Francesca Palmiotto; Derya Ozkul (German Law Journal)
Strategic litigation plays a crucial role in advancing human rights in the digital age, particularly in cases where data subjects, such as migrants and protection seekers, experience significant power imbalances. In this Article, we consider strategic litigation as part of broader legal mobilization efforts. Although some emerging studies have examined contestation against digital rights and migrant rights separately using legal mobilization frameworks, scholarship on legal mobilization concerning the use of automated systems on migrants and asylum seekers is scarce. This Article aims to address this gap by investigating the extent to which EU law empowers strategic litigants working at the intersection of technology and migration. Through an analysis of five specific cases of contestation and in-depth interviews, we explore how EU data protection law is leveraged to protect the digital rights of migrants and asylum seekers. This analysis takes a socio-legal perspective, analyzing the opportunities presented by EU data protection law and how civil society organizations (CSOs) utilize them in practice. Our findings reveal that the pre-litigation phase is particularly onerous for strategic litigants in this field, requiring a considerable investment of resources and time before even reaching the litigation stage. We illustrate this phase as akin to “climbing a wall,” characterized by numerous hurdles that CSOs face and the strategies they employ to overcome them.